The design of additional public transport services to increase the resilience of road networks - De Matteis, Luca; Strano, Salvatore; D’Acierno, Luca (International Conference “Environmental Engineering”, 2023)
Some events (as, for instance, a bridge collapse, an underpass closure or a road maintenance intervention) may generate the total or partial unavailability of some elements of urban road networks. Hence, some users have to redirect their paths generating an increase in congestion on the remaining part of the network. In this context, this paper proposes the design of additional public transport services to increase the resilience of road urban networks by affecting the user modal choices to reduce road flows and bring congestion levels as close as possible to the initial equilibrium conditions. Finally, to verify the usefulness and feasibility of the proposed methodology, it has been applied in the case of the road network of Fuorigrotta, a district of the city of Naples, in southern Italy.